Clues for a possible role of senescent T cells in giant cell arteritis pathogenesis. (22nd February 2011) - van der Geest, K S M; Abdulahad, W H; Huitema, M G; Kroesen, B J; Brouwer, E; Boots, A M H
Abstract : Background and objectives: T cells are considered major players in the development of giant cell arteritis (GCA). To date most attention has been focused on Th1 and Th17 cells. However, the contribution of senescent T cells to this strictly ageing-associated vasculitis remains obscure. The purpose of this study was to provide clues whether senescent T cells play a role in GCA pathogenesis. Therefore we assessed frequencies of senescent T cells and their expression of the natural killer marker CD161 in patients with GCA and healthy controls. CD161 has been reported to identify cells with a pro-inflammatory cytokine repertoire (eg, interferon γ and interleukin 17). Methods: Peripheral blood of seven untreated GCA-patients and eight age/sex matched healthy controls was obtained. Using flow cytometry, senescent (or terminally differentiated) T cells were defined as CD45RO-CCR7- cells within the CD4 and CD8 T cell gates. In addition, the naïve (CD45RO-CCR7+), central memory (CD45RO+CCR7+) and effector memory (CD45RO+CCR7-) T cell subsets were identified. Expression of CD161 was assessed in each of these subsets. Results: Frequencies of senescent, naïve and central memory CD4 T cells were similar in GCA-patients and controls, whereas a trend towards decreased CD4 effector memory cells was observed in patients (23% vs 34%). The CD4 senescent T cell subset of GCA patients contained more CD161 cells compared to healthy controls (4, 4% vs 1, 6%). Also in the CD4 effector memory subset of patients we observed a trend towards more CD161 cells (33% vs 21%). Frequencies of CD8 naïve, central memory, effector memory and terminally differentiated subsets were similar in patients and controls. In addition no differences were found for CD161 expression in CD8 T cells. Conclusion: We found one clue suggesting a role for senescent T cells in GCA: namely, an increased expression of CD161 by CD4 senescent T cells in GCA patients. This could reflect a natural killer-like phenotype in these cells, associated with high production of IFNγ and cytotoxic effector molecules. The same might be true for the CD4 effector memory subset of GCA patients, since we observed a trend towards more CD161 expression in these cells. In addition we found a trend towards decreased frequencies of circulating CD4 effector memory cells in GCA-patients. This may suggest that these cells preferentially migrate to the site of inflammation, as previously observed in Wegener's granulomatosis.1